Sektor Usaha Kecil dan Menengah dan Efektivitasnya dalam Penyerapan Tenaga Kerja - Romualdus Turu Putra (Musamus Journal of Economics Development, 2023)
ABSTRAC This study aims to determine and analyze the Number of Business Units (SMEs), Investment Value, and Minimum Wage on Labor Absorption in Merauke Regency from 2012 to 2021. The data used in this study are secondary data. Data is analyzed using quantitative methods, and the technique used is multiple linear regression analysis with the assistance of SPSS application version 21. The results of the study show that the number of Business Units (SMEs) has a positive and significant influence on Labor Absorption, with a coefficient value of 1.216 and a significance value of 0.021. The Investment Value variable has a negative and insignificant influence on Labor Absorption with a coefficient value of -3.364 and a significance value of 0.015, while the Minimum Wage variable has a negative and insignificant influence on Labor Absorption with a coefficient value of -0.458 and a significance value of 0.526. Simultaneously, the number of Business Units (SMEs), Investment Value, and Minimum Wage have an influence on Labor Absorption in Merauke Regency. Keywords: Number of Bisiness Units (SMEs), Investment Value, Minimum Wage, Labor Absorption.